Catalyst for hydrogen storage material as well as preparation method and application of catalyst

The catalyst Ni@CSs is prepared by wrapping Ni nanoparticles on a carbon support and applied to Mg-based hydrogen storage materials through ball milling method, which solves the problems of high hydrogen release temperature and slow kinetics of magnesium-based solid hydrogen storage materials, and achieves a more efficient hydrogen absorption and discharge process and better cycling performance.

CN119897109APending Publication Date: 2025-04-29CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES +1

Patent Information

Application Number
CN202510376432.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The high hydrogen release temperature and slow low temperature kinetics of magnesium-based solid hydrogen storage materials limit their promotion and application in industrial and civil fields.

Method used

Nickel chloride hexahydrate, polyether P123, polyether P127, dopamine hydrochloride, 1,3,5-tritylene and ammonia water were used as raw materials to wrap elemental Ni nanoparticles on a carbon support, and catalyst Ni@CSs were prepared, and uniformly dispersed on the Mg surface by ball milling.

Benefits of technology

It significantly reduces the initial hydrogen release temperature of Mg, improves the diffusion rate of hydrogen and hydrogen storage kinetic activity, enhances the circulation performance of Mg, and has a simple process and cheap raw materials, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897109A_ABST
    Figure CN119897109A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for a hydrogen storage material as well as a preparation method and application thereof, and belongs to the technical field of hydrogen storage materials and preparation thereof. The problems that an existing magnesium-based solid hydrogen storage material is high in hydrogen desorption temperature, slow in low-temperature dynamics and the like are solved. According to the invention, nickel chloride hexahydrate, polyether P123, polyether P127, dopamine hydrochloride, 1, 3, 5-trimethylbenzene and ammonia water are used as raw materials to prepare the catalyst which takes carbon as a carrier to wrap elemental Ni nanoparticles. The catalyst is applied to an Mg-based hydrogen storage material through a ball-milling method, and in the ball-milling mixing process, the carbon carrier can also serve as a grinding aid to inhibit Mg powder agglomeration and promote better combination between Mg and Ni, and meanwhile, the cycle performance of Mg powder hydrogen storage is improved. Mg2NiH4 / Mg2Ni generated in situ in the hydrogen absorption and desorption process inherits the superfine size and uniform dispersity of Ni nanoparticles, and shows high activity in the hydrogen absorption and desorption cycle of Mg.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst for hydrogen storage material and a preparation method and application thereof, belonging to the technical field of hydrogen storage material and preparation thereof. Background Art

[0002] Hydrogen energy has become a renewable energy with great prospects due to its high energy density, high combustion calorific value and clean and pollution-free advantages. However, the hydrogen transportation process faces many challenges, which is the main bottleneck for the wider application and in-depth development of hydrogen energy. Solid-state hydrogen storage technology is recognized as a more promising option compared to compressed gaseous hydrogen storage or liquid hydrogen storage due to its high density, high safety and convenience.

[0003] As a hydrogen storage material, magnesium (Mg) has outstanding characteristics such as high hydrogen storage capacity (mass fraction can reach 7.6%), low cost and environmental friendliness, which has attracted widespread attention in the field of hydrogen storage materials. However, the Mg / MgH2 system has problems such as high operating temperature and slow reaction kinetics, which seriously restricts its further promotion and application in industrial and civilian fields.

[0004] Catalysis, nano-sizing and alloying are widely considered to be effective strategies for optimizing the performance of magnesium-based hydrogen storage materials. Among these strategies, adding a small amount of catalyst is one of the simplest and most efficient methods. Due to the sequential filling of valence electrons in the d orbital when transition metals gain electrons, they are endowed with excellent catalytic efficiency for these Mg-based hydrogen storage materials. Nickel (Ni), as a transition metal element, has a d orbital that can interact with the antibonding orbital of hydrogen. It can generate Mg2NiH4 / Mg2Ni during the absorption and desorption of hydrogen, effectively promote the diffusion of hydrogen, and show excellent catalytic effects. Therefore, it is very necessary to provide a Ni-containing catalyst for further improving the thermal / kinetic properties of Mg. Summary of the invention

[0005] Aiming at the problems of high hydrogen desorption temperature and slow low-temperature kinetics of existing magnesium-based solid hydrogen storage materials, the present invention provides a catalyst for hydrogen storage material and a preparation method and application thereof.

[0006] The technical solution of the present invention: One of the purposes of the present invention is to provide a method for preparing a catalyst for a hydrogen storage material, the method comprising the following steps: (1) dissolving nickel chloride hexahydrate in a mixed solvent, adding polyether P123, polyether P127, dopamine hydrochloride and 1,3,5-trimethylbenzene, stirring evenly at room temperature, then adding ammonia water, stirring to obtain a precursor solution, centrifuging, filtering, and drying to obtain a precursor powder; (2) The precursor powder is calcined in an inert gas atmosphere to obtain a catalyst for hydrogen storage material, named Ni@CSs.

[0007] It is further defined that the mixed solvent in (1) is composed of water and ethanol in a volume ratio of 1:1.

[0008] It is further defined that the mass ratio of nickel chloride hexahydrate, polyether P123, polyether P127 and dopamine hydrochloride in (1) is (1.19-4.75): 1:3:6.

[0009] It is further defined that the volume ratio of 1,3,5-trimethylbenzene, aqueous ammonia and the mixed solvent in (1) is 1:1:25.

[0010] It is further defined that the inert gas in (2) is argon.

[0011] It is further defined that the calcination process in (2) is: keeping at 350°C for 2 hours, heating to 800°C and keeping at this temperature for 2 hours.

[0012] The second object of the present invention is to provide a Ni@CSs powder as a catalyst for hydrogen storage material prepared by the above method, wherein the Ni@CSs powder as a catalyst for hydrogen storage material is a spherical particle with a diameter of 300-600 nm.

[0013] The third object of the present invention is to provide a composite hydrogen storage material, which is prepared using Ni@CSs powder and Mg powder, a catalyst for hydrogen storage materials, as raw materials.

[0014] It is further defined that the Mg powder is spherical particles having a size of 200 mesh.

[0015] It is further defined that the Ni@CSs powder accounts for 2.5~3.5wt.% in the composite hydrogen storage material.

[0016] A fourth object of the present invention is to provide a method for preparing the above-mentioned composite hydrogen storage material, which comprises: mechanically mixing Ni@CSs powder and Mg powder by intermittent ball milling under a protective atmosphere.

[0017] It is further defined that the intermittent ball milling method is to mill for 5 minutes each time and rest for 10 minutes, the total ball milling time is 3 to 5 hours, the ball-to-material ratio is 40:1, and the ball milling speed is 300 to 500 rpm.

[0018] Beneficial effects: The present invention uses nickel chloride hexahydrate, polyether P123, polyether P127, dopamine hydrochloride, 1,3,5-trimethylbenzene and ammonia water as raw materials to prepare a catalyst in which single Ni nanoparticles are wrapped with carbon as a carrier. The catalyst is applied to Mg-based hydrogen storage materials by ball milling, and can be evenly dispersed on the Mg surface. In the process of ball milling and mixing, the carbon carrier can also act as a grinding aid to inhibit the agglomeration of Mg powder, promote better bonding between Mg and Ni, and improve the cycle performance of Mg powder hydrogen storage. The hydrogen storage material obtained by compounding the catalyst with commercial Mg powder, Mg2NiH4 / Mg2Ni generated in situ during the process of hydrogen absorption and desorption, inherits the ultrafine size and uniform dispersion of Ni nanoparticles, and accelerates the Mg hydrogen storage kinetics as a "hydrogen pump", showing high activity in the hydrogen absorption and desorption cycle of Mg, and can reduce the initial hydrogen desorption temperature of commercial Mg powder to 225°C. At 330°C, 5wt.% of hydrogen can be released in only 4 minutes. At the same time, the activation energy of hydrogen desorption is only 77.48kJ / mol. After ten cycles, the capacity retention rate is as high as 93.5%. In addition, the preparation process of the composite hydrogen storage material provided by the present invention is simple and mature, and the raw materials are cheap and easily available. Only a small amount of Ni@CSs needs to be added to significantly improve the hydrogen storage performance of Mg, which is convenient for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Ni prepared in Example 1 0.01 @ Transmission electron microscope image of CSs; Figure 2 Ni prepared in Example 1 0.01 High-resolution transmission electron microscopy images of @CSs; Figure 3 Ni prepared in Example 1 0.01 @X-ray diffraction pattern of CSs; Figure 4 Ni prepared in Example 1 0.01 @CSs X-ray photoelectron spectrum; Figure 5 A comparison diagram of the programmed temperature dehydrogenation curves of the composite hydrogen storage materials prepared in Example 1 and Comparative Examples 1-2; Figure 6 It is a comparison diagram of isothermal hydrogen absorption curves of the composite hydrogen storage materials prepared in Example 1 and Comparative Examples 1-2 at 400° C. and 3 MPa hydrogen pressure; Figure 7 It is a comparison diagram of isothermal hydrogen release curves of the composite hydrogen storage materials prepared in Example 1 and Comparative Example 2 at a hydrogen pressure of 0.0001 MPa and different temperatures; Figure 8 A comparison diagram of the activation energy of hydrogen release of the composite hydrogen storage materials prepared in Example 1 and Comparative Example 2; Fig. 9 This is the cyclic hydrogen absorption / desorption diagram of the composite hydrogen storage material prepared in Example 1. DETAILED DESCRIPTION

[0020] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0021] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0022] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0023] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.

[0024] Example 1 In this example, Ni is used to prepare the hydrogen storage material catalyst 0.01 @CSs powder method steps are as follows: First, 0.01 mol of nickel chloride hexahydrate was dissolved in a mixed solution of water and ethanol (volume ratio 1:1) and ultrasonicated for 10 min.

[0025] Next, 0.25 g of polyether P123, 0.75 g of polyether P127, 1.5 g of dopamine hydrochloride and 4 mL of 1,3,5-trimethylbenzene were added to the above mixed solution and stirred vigorously at room temperature.

[0026] Then, 4 mL of ammonia water was added under magnetic stirring and stirred for 2 h to obtain Ni 0.01 @CSs precursor solution.

[0027] Subsequently, the solid product was collected by centrifugation (9000 rpm, 3 min), washed three times with ethanol and deionized water respectively, and dried in an oven at 60 °C overnight to obtain Ni 0.01 @CSs precursor powder.

[0028] Finally, under argon atmosphere, Ni 0.01 @CSs precursor powder was first calcined at 350℃ for 2h, then heated to 800℃ for 2h, and finally Ni 0.01 @CSs powder.

[0029] The Ni prepared in this example 0.01 The microstructure of @CSs powder was characterized. Figure 1 and Figure 2 shown. Figure 1 For you 0.01 Transmission electron microscopy image of @CSs powder, by Figure 1 You know 0.01 @CSs powder is spherical, and the size of Ni particles is 3~8nm. Figure 2 For you 0.01 High-resolution transmission electron micrograph of @CSs powder, Figure 2 It can be seen that the Ni nanoparticles are covered inside the carbon.

[0030] Furthermore, Figure 3 For you 0.01 X-ray diffraction pattern of @CSs powder, Figure 3 It can be seen that Ni 0.01 The diffraction peaks of @CSs powder at 2θ of 44.48°, 51.83°, and 76.35° are in good agreement with the Ni standard spectrum, while the diffraction peak associated with the carbon structure appears near 26°. Figure 4 For you 0.01 @CSs powder X-ray photoelectron spectrum of C 1s and Ni 2p c 1s, Figure 4 It fully illustrates Ni 0.01 In the @CSs catalyst, C and Ni are not bonded, and Ni is encapsulated inside C in the form of a single substance.

[0031] This example prepares the composite hydrogen storage material Mg-Ni 0.01 @CSs's method steps are as follows: Under argon atmosphere, Ni 0.01 @CSs powder and Mg powder were mixed in a mass ratio of 3:100. A certain amount of zirconia beads were weighed according to a ball-to-material ratio of 40:1. The beads were placed in a ball mill and ball milled at a speed of 400 rpm. Intermittent ball milling was used, with each ball milling lasting 5 minutes and resting for 10 minutes. The total ball milling time was 4 hours to obtain a composite hydrogen storage material named Mg+Ni@CSs.

[0032] Comparative Example 1 The difference between this comparative example and Example 1 is that Ni is not added. The specific method steps for preparing the catalyst CSs powder for hydrogen storage material are as follows: First, 0.25 g of polyether P123, 0.75 g of polyether P127, 1.5 g of dopamine hydrochloride and 4 mL of 1,3,5-trimethylbenzene were added to a mixed solution of water and ethanol (volume ratio 1:1), and stirred vigorously at room temperature until the solution was mixed evenly.

[0033] Next, 4 mL of aqueous ammonia was added to the mixture under magnetic stirring and stirred for 2 h to obtain a CSs precursor solution.

[0034] Subsequently, the solid product was collected by centrifugation (9000 rpm, 3 min), washed three times with ethanol and deionized water respectively, and the obtained solid product was placed in an oven at 60 °C for overnight to obtain CSs precursor powder.

[0035] Finally, under an argon atmosphere, the CSs precursor powder was first calcined at 350°C for 2 h, and then heated to 800°C for calcination for 2 h to finally obtain CSs powder.

[0036] The method steps for preparing the composite hydrogen storage material Mg-CSs in this comparative example are as follows: Under argon atmosphere, CSs powder and Mg powder were mixed in a mass ratio of 3:100. A certain amount of zirconia beads were weighed according to a ball-to-material ratio of 40:1. The beads were placed in a ball mill and ball milled at a speed of 400 rpm. Intermittent ball milling was used, with each ball milling lasting 5 min and resting for 10 min. The total ball milling time was 4 h to obtain a composite hydrogen storage material named Mg+CSs.

[0037] Comparative Example 2 The method steps for preparing the composite hydrogen storage material BM-Mg in this comparative example are as follows: Under argon atmosphere, a certain amount of Mg powder and zirconia beads were weighed according to a mass ratio of 40:1, placed in a ball mill, and ball milled at a speed of 400 rpm. Intermittent ball milling was adopted, with each ball milling for 5 minutes and resting for 10 minutes. The total ball milling time was 4 hours to obtain a composite hydrogen storage material, named BM-Mg.

[0038] The hydrogen storage performance of the composite hydrogen storage material Mg+Ni@CSs prepared in Example 1, the composite hydrogen storage material Mg+CSs prepared in Comparative Example 1, and the composite hydrogen storage material BM-Mg prepared in Comparative Example 2 were evaluated, and the evaluation results are shown below.

[0039] Figure 5 The temperature-programmed hydrogen release curves of the composite hydrogen storage materials prepared in Example 1 and Comparative Examples 1-2 are compared. Figure 5It can be seen that the initial dehydrogenation temperature of the Mg+Ni@CSs composite hydrogen storage material dropped to 225°C, which is about 129°C lower than that of pure BM-Mg (the initial dehydrogenation temperature of BM-Mg is 354°C), showing the most excellent dehydrogenation thermodynamic properties. The initial dehydrogenation temperature of the Mg+CSs composite hydrogen storage material dropped to 342°C, which is still higher than that of the Mg+Ni@CSs composite hydrogen storage material.

[0040] Figure 6 The isothermal hydrogen absorption curves of the composite hydrogen storage materials prepared in Example 1 and Comparative Examples 1-2 at 400°C and 3MPa hydrogen pressure are compared. Figure 6 It can be seen that Mg+Ni@CSs can absorb 5.3wt.% hydrogen in 10 minutes at 400℃ and 3MPa. The hydrogen absorption of Mg+CSs composite hydrogen storage material is 3.7wt.%, which is lower than that of Mg+Ni@CSs composite hydrogen storage material. BM-Mg only absorbs 2.1wt.% hydrogen in 10 minutes.

[0041] Figure 7 The isothermal hydrogen release curves of the composite hydrogen storage materials prepared in Example 1 and Comparative Example 2 at 0.0001 MPa hydrogen pressure and different temperatures are compared. Figure 7 It can be seen that the Mg+Ni@CSs composite hydrogen storage material releases up to 4wt.% of hydrogen within 1 hour at 270℃, and 5wt.% of hydrogen can be released in just 4 minutes at 330℃. BM-Mg can hardly release hydrogen below 300℃, and even at 330℃, it can only release 2.3wt.% of hydrogen within 1 hour.

[0042] Figure 8 The comparison diagram of the activation energy of hydrogen release of the composite hydrogen storage material prepared in Example 1 and Comparative Example 2 is shown in FIG. Figure 8 It can be seen that the dehydrogenation activation energy of Mg+Ni@CSs composite hydrogen storage material is 77.48 kJ / mol. The dehydrogenation activation energy of BM-Mg is 107.25 kJ / mol.

[0043] Fig. 9 The cyclic absorption / desorption diagram of the composite hydrogen storage material prepared in Example 1 is shown in FIG. Fig. 9 It can be seen that the retention rate of Mg+Ni@CSs composite hydrogen storage material is as high as 93.5% after 10 cycles.

[0044] Although the present invention has been disclosed as above in the preferred embodiments, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a catalyst for hydrogen storage material, characterized in that: include: (1) dissolving nickel chloride hexahydrate in a mixed solvent, adding polyether P123, polyether P127, dopamine hydrochloride and 1,3,5-trimethylbenzene, stirring evenly at room temperature, then adding ammonia water, stirring to obtain a precursor solution, centrifuging, filtering, and drying to obtain a precursor powder; (2) The precursor powder is calcined in an inert gas atmosphere to obtain a catalyst for hydrogen storage material, named Ni@CSs.

2. The preparation method according to claim 1, characterized in that: The mixed solvent in (1) is prepared by mixing water and ethanol in a volume ratio of 1:

1.

3. The preparation method according to claim 1, characterized in that: (1) The mass ratio of nickel chloride hexahydrate, polyether P123, polyether P127 and dopamine hydrochloride is (1.19-4.75): 1:3:

6.

4. The preparation method according to claim 1, characterized in that: In (1), the volume ratio of 1,3,5-trimethylbenzene, aqueous ammonia and mixed solvent is 1:1:

25.

5. The preparation method according to claim 1, characterized in that: (2) The inert gas is argon.

6. The preparation method according to claim 1, characterized in that: (2) The calcination process is as follows: keep at 350°C for 2 hours, then raise the temperature to 800°C and keep for 2 hours.

7. A Ni@CSs catalyst powder for hydrogen storage material prepared by the method according to any one of claims 1 to 6, characterized in that: Ni@CSs powder is spherical particles with a diameter of 300~600nm.

8. A composite hydrogen storage material, characterized in that: The catalyst for hydrogen storage material according to claim 7 is prepared using Ni@CSs powder and Mg powder as raw materials.

9. The composite hydrogen storage material according to claim 8, characterized in that: Ni@CSs powder accounts for 2.5~3.5wt.% in the composite hydrogen storage material.

10. A method for preparing the composite hydrogen storage material according to claim 9, characterized in that: Ni@CSs powder and Mg powder were mechanically mixed by intermittent ball milling under protective atmosphere.

Citation Information

Patent Citations

  • Carbon-supported nickel catalyst-doped Mg(BH4)2-based hydrogen storage material and preparation method thereof

    CN108394860A

  • Nitrogen and sulfur co-doped hierarchical porous carbon composite material, and preparation method and application thereof

    CN110627033A

  • Transition metal-N / S co-doped porous mulberry-shaped carbon material catalyst as well as preparation and application thereof

    CN111326748A

  • Carbon-loaded high-entropy alloy composite magnesium-based hydrogen storage material and preparation method thereof

    CN113912006A

  • Metal oxide-carbon-based composite material with bowl-shaped structure as well as preparation method and application of metal oxide-carbon-based composite material

    CN114890458A

Cited By

  • Catalyst for hydrogen storage material as well as preparation method and application of catalyst

    CN121869389A

  • Catalyst for hydrogen storage material, its preparation method and application

    CN121869389B